The cytoprotective effect of different doses of Sildenafil on indomethacin-induced gastric mucosal damage in rats: - Matloub, Samir Y. N.; Manna, Mohammed J. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Sildenafil, a selective phosphodiesterase -5 (PDE-5) inhibitor increases cyclic guanosine monophosphate (cGMP) and amplifies many biological actions of nitric oxide (NO) which is an important mediator of gastric mucosal defense ; was evaluated in this study using different doses for its cytoprotective effect on gastric mucosal damage induced by indomethacin . We also evaluated the effect of this drug on NO production, Prostaglandin E2 (PGE2) synthesis, Myeloperoxidase (MPO) activity, and Interlukin-4 (IL-4) expression.Methods: The study was performed between April and July 2008 in the Department of Pharmacology / College of Medicine /Baghdad University .It was conducted on 80 adult male albino rats, divided into 8 groups, the first served as a control received the vehicle, the second received indomethacin orally of 60mg/kg .The third and fourth groups were pretreated 30 minutes prior indomethacin with oral sildenafil 10 and 20mg/kg respectively. The other groups were pretreated 30 minutes prior to sildenafil (10and20mg/kg) with intraperitoneal NG-L-Arginine Methyl Ester (L-NAME) 20mg/kg with or without L-Arginine. The rats were then sacrificed after 4 hours and their stomachs were isolated and submitted to macroscopical assessment and for the measurement of the gastric PGE2, MPO, and IL-4.Results: Sildenafil (10 and 20 mg/kg) pretreatment resulted in a significant (p